KEEFEKTIFAN MODEL PEMBELAJARAN MIND MAPPING PADA PEMBELAJARAN IPA PADA SISWA KELAS V DI SD NEGERI 010 TALONTAM KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Yusneti Yusneti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The problem behind this research is the low learning outcomes of science in fifth grade students of SDN 010 Talontam, Benai sub-district. This study aims to improve the learning system and improve science learning outcomes by applying mind mapping learning models. . Class action research is an effort to improve various kinds of learning problems in the classroom. Data analysis of teacher activity after the study is in the initial data of 60%, then the second meeting is 70.6%, the third meeting is 84%, and at the fourth meeting is 90%. Student activity data after research has increased at the first meeting only by 56%, at the second meeting amounting to 64.5, at the third meeting at 81%, and at the IV meeting at 85%. Improvement of learning outcomes is obtained after a daily test, in UH I the average student learning outcomes are 73 and in UH II 87 is a significant increase. By looking at the data above that the application of mind mapping learning models is effective for improving Indonesian learning outcomes in fifth grade students of SDN 010 Talontam.